2016
DOI: 10.1111/cas.13083
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits estrogen‐dependent endometrial cancer cell growth by activating the AMPKFOXO1 signal pathway

Abstract: Metformin is an oral biguanide commonly used for treating type II diabetes and has recently been reported to possess antiproliferative properties that can be exploited for the prevention and treatment of a variety of cancers. The mechanisms underlying this effect have not been fully elucidated. Our study shows a marked loss of AMP‐activated protein kinase (AMPK) phosphorylation and nuclear human Forkhead box O1 (FOXO1) protein in estrogen‐dependent endometrial cancer (EC) tumors compared to normal control endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 51 publications
0
34
0
1
Order By: Relevance
“…FOXO1 is also largely known as an important transcription factor to induce autophagy (38). The activation of AMPK can regulate the activation of FOXO1 (39,40). However, our results reveal that CD36 knockdown in HepG2 cells reduces the mRNA and protein expression of FOXO1 but increases the level of p-FOXO1.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…FOXO1 is also largely known as an important transcription factor to induce autophagy (38). The activation of AMPK can regulate the activation of FOXO1 (39,40). However, our results reveal that CD36 knockdown in HepG2 cells reduces the mRNA and protein expression of FOXO1 but increases the level of p-FOXO1.…”
Section: Discussionmentioning
confidence: 60%
“…However, our results reveal that CD36 knockdown in HepG2 cells reduces the mRNA and protein expression of FOXO1 but increases the level of p-FOXO1. Several studies have reported that cytoplasmic p-FOXO1 is inactivated (37,39). However, Wang et al (41) noted that p-FOXO1 is located in the cytoplasm of iNKs and interacts with ATG7, leading to the induction of autophagy, which was independent of the transcriptional activity of FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 proteins are regulated by phosphorylation, ubiquitination, and acetylation via several kinases [25]. By contrast, AMPPK and JNK were suggested to induce nuclear translocation and activation of FOXO1 proteins [26]. In addition, FOXO transcription factors regulate different cellular processes, such as inhibition of proliferation, induction of differentiation or apoptosis, and protection against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a common insulin-sensitizing agent used to treat type II diabetes. However, accumulating evidence indicated that metformin could be applied in the treatment of some malignant diseases including EC (28)(29)(30). Firstly, as an insulin-sensitizing agent, metformin decreased the circulating insulin levels by inhibiting the hepatic glucose and lipid synthesis, as well as by increasing muscle glucose uptake.…”
Section: Discussionmentioning
confidence: 99%